The night travelers : a novel - Correa, Armando Lucas, 1959- (Atria Books, 2023)
Separated by time but united by sacrifice, four women experience love, loss, war, and hope from the rise of Nazism to the fall of the Berlin Wall as they embark on journeys of self-discovery and find themselves to be living testaments to the power of maternal love.